2020
DOI: 10.1029/2019gl085938
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Marine Plankton Ecosystems Are Not Observed in Freshly Emitted Sea Spray Aerosol Over the North Atlantic Ocean

Abstract: Sea spray aerosol (SSA) consists of both sea salt and organic components. These aerosols affect Earth's climate by scattering solar radiation and by altering cloud properties. Here we present observations of SSA particles generated at sea using an over‐the‐side bubbling system (Sea Sweep) and an onboard plunging wave mesocosm (Marine Aerosol Reference Tank—MART) during five cruises in the North Atlantic. The cruises were timed to sample different stages of the North Atlantic plankton bloom and included transec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 79 publications
4
43
0
Order By: Relevance
“…Shipboard measurements in open ocean conditions from multiple oceans do not support a hypothesized link between primary ocean production and organic enrichment of the aerosol (Beaupré et al, 2019;Kasparian et al, 2017;Keene et al, 2017;Kieber et al, 2016;Quinn et al, 2014Quinn et al, , 2019. For example, Quinn et al (2014) and Bates et al (2020) used sea sweep (a floating bubbler that generates and samples sea-spray particles) and reported no statistically significant differences in the organicto-sodium content of the generated submicron aerosol particles in oligotrophic and eutrophic waters in the Western Atlantic and Eastern Pacific oceans. Russell et al (2010) found that sea-spray organic mass (OM) correlated with local wind speed but not with chlorophyll concentrations for marine periods in the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…Shipboard measurements in open ocean conditions from multiple oceans do not support a hypothesized link between primary ocean production and organic enrichment of the aerosol (Beaupré et al, 2019;Kasparian et al, 2017;Keene et al, 2017;Kieber et al, 2016;Quinn et al, 2014Quinn et al, , 2019. For example, Quinn et al (2014) and Bates et al (2020) used sea sweep (a floating bubbler that generates and samples sea-spray particles) and reported no statistically significant differences in the organicto-sodium content of the generated submicron aerosol particles in oligotrophic and eutrophic waters in the Western Atlantic and Eastern Pacific oceans. Russell et al (2010) found that sea-spray organic mass (OM) correlated with local wind speed but not with chlorophyll concentrations for marine periods in the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results based on artificial bubbling of seawater in the open ocean indicate that biological productivity has a minor influence on sea spray organic carbon and its cloud condensation nuclei (CCN) properties, suggesting that the organics associated with sea spray are derived from long-lived, well-distributed marine DOM (Bates et al, 2020;Russell et al, 2010). Beaupré et al (2019) reported that highly aged DOM carbon could account for 19 %-40 % of the organic carbon in artificially generated sea spray. Ceburnis et al (2016) found that most organic enrichment in marine aerosol over the southern Indian Ocean was attributable to fresh POM.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have indicated that aged organic matter, such as that metabolized by heterotrophic bacteria, is effectively transferred to the aerosol phase (Cochran et al, 2017;Wang et al, 2015). However, Beaupré et al (2019) determined that up to 40 % of the organic carbon in sea spray could be highly aged and that the composition of SSA could be less strongly influenced by rates of primary biological productivity in the underlying seawater. Other studies have found that the organic enrichment of SSA is attributable to freshly produced fixed carbon and that SSA carbon content is correlated with chlorophyll concentration (Ceburnis et al, 2016;O'Dowd et al, 2015).…”
mentioning
confidence: 99%